2000
DOI: 10.3322/canjclin.50.3.184
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis and management of ductal carcinoma in-situ of the breast

Abstract: The widespread utilization of screening mammography has produced a shift in the stage of breast cancer at diagnosis in the US: Currently, 12% to 15% of newly diagnosed breast cancer cases annually are ductal carcinoma in-situ (DCIS). The diagnosis is made, in at least 90% of patients, with mammography. Only about 10% of patients will have a palpable mass. The accurate characterization and visualization of calcifications typically requires magnification of mammographic imaging. The morphology of the calcificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
7

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 18 publications
0
40
0
7
Order By: Relevance
“…DCIS accounts for 12-15% of newly diagnosed breast cancer cases, about 39,000 per year in the United States (Winchester et al, 2000;Silverstein, 2000). A better understanding of the relationship between non-invasive and invasive breast lesions could yield improvements in prevention, diagnosis, and treatment (Fisher, 1996;O'Shaughnessy et al, 2002;Hong, 2002, Burstein et al, 2004).…”
Section: Article In Pressmentioning
confidence: 99%
“…DCIS accounts for 12-15% of newly diagnosed breast cancer cases, about 39,000 per year in the United States (Winchester et al, 2000;Silverstein, 2000). A better understanding of the relationship between non-invasive and invasive breast lesions could yield improvements in prevention, diagnosis, and treatment (Fisher, 1996;O'Shaughnessy et al, 2002;Hong, 2002, Burstein et al, 2004).…”
Section: Article In Pressmentioning
confidence: 99%
“…18 Of the 1026 control subjects from Los Angeles County who were eligible for the current BCIS study, 410 (40%) reported that they had not received a mammogram within 2 years before their reference dates. Because the majority of newly diagnosed patients with BCIS have no palpable lesions and are diagnosed by mammography, 3,19 we limited control subject eligibility to those who reported receiving a mammogram within the 2 years before the reference date (n ϭ 616).…”
Section: Study Backgroundmentioning
confidence: 99%
“…10,15 The COC has also been a collaborator in the development of consensus standards for the diagnosis and management of breast cancer. [23][24][25] The most recent update noted that "mastectomy (either radical or modified radical) was the historical mainstay of the treatment of stage I and stage II breast cancer for decades." It further stated that "Although mastectomy continues to be appropriate for some patients, breast conservation has become the preferred method of treatment for many patients."…”
mentioning
confidence: 99%